The Effect of Empowering Rhythmic Gymnastics on the Fitness of PKK Women in Karangduren Village, Pakisaji Health Center Working Area, Malang Regency - Amellia Trisya Yuliastika; Sugianto Hadi; Wandi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Fitness is the quality of a person to carry out activities according to their work optimally without causing health problems and excessive fatigue. PKK meeting activities in Karangduren Village RT 07 are still considered general, such as social gatherings and cooperative savings and loans & shares from members. So PKK activities in the form of physical activities such as gymnastics are still not implemented in improving the fitness of PKK woman. Objective: The purpose of this research is to determine The Effect of Empowering Rhythmic Gymnastics on the Fitness of PKK Women in Karangduren Village, Pakisaji Health Center Working Area, Malang Regency. Method: This type of research is quantitative Pre-Experimental with a One Group Pre Test Post Test design. The research sample used a total sampling of 32 PKK woman. Result: The research results showed that the average fitness score of PKK woman before empowerment was 72.93 and the fitness of PKK woman after empowerment was 81.04. From the results of the Wilcoxon analysis, it was found that p = 0.001, meaning that the p value < ? value (0.05) means that H1 is accepted, meaning that there is an The Effect of Empowering Rhythmic Gymnastics on the Fitness of PKK Women in Karangduren Village, Pakisaji Health Center Working Area, Malang Regency. Conclusion: It can be concluded that there is an The Effect of Empowering Rhythmic Gymnastics on the Fitness of PKK Women in Karangduren Village, Pakisaji Health Center Working Area, Malang Regency.